Changes in structure and function of social networks of independently living middle-aged and older adults in diverse sociodemographic subgroups during the COVID-19 pandemic: a longitudinal study - Lisanne CJ Steijvers; Stephanie Brinkhues; Theo G van Tilburg; Christian JPA Hoebe; Mandy MN Stijnen; Nanne de Vries; Rik Crutzen; Nicole HTM Dukers-Muijrers (BMC, 2022)
Abstract Background Social networks, i.e., all social relationships that people have, contribute to well-being and health. Governmental measures against COVID-19 were explicitly aimed to decrease physical social contact. We evaluated ego-centric social network structure and function, and changes therein, among various sociodemographic subgroups before and during the COVID-19 pandemic. Methods Independently living Dutch adults aged 40 years and older participating in the SaNAE longitudinal cohort study filled in online questionnaires in 2019 and 2020. Changes in network size (network structure) and social supporters (network function) were assessed. Associations with risk for changes (versus stable) were assessed for sociodemographic subgroups (sex, age, educational level, and urbanization level) using multivariable regression analyses, adjusted for confounders. Results Of 3,344 respondents 55% were men with a mean age of 65 years (age range 41-95 in 2020). In all assessed sociodemographic subgroups, decreases were observed in mean network size (total population: 11.4 to 9.8), the number of emotional supporters (7.2 to 6.1), and practical supporters (2.2 to 1.8), and an increase in the number of informational supporters (4.1 to 4.7). In all subgroups, the networks changed to being more family oriented. Some individuals increased their network size or number of supporters; they were more often women, higher-educated, or living in rural areas. Conclusion The COVID-19 pandemic impacted social networks of people aged 40 years and older, as they increased informational support and reduced the number of their social relationships, mainly in terms of emotional and practical supporters. Notably, some individuals did not show such unfavorable trends and managed to reorganize their networks to attribute social support roles more centrally.